Relation of powers in gymnastics in the pre-olympic season in light of international sanctions against russian athletes - Pakholkova N.V.; Somkin A.A.; Zarodnyuk G.V.; Larionova M.N. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to conduct a comparative analysis of the results shown by the strongest national teams at the 2023 World Championships and Russian gymnasts at the Russian Cup to determine competitiveness in the international arena under sanctions. Methods and structure of the study. Analysis of information materials on websites: IOC (olympics.com), FIG (gymnastics.sport), Russian Artistic Gymnastics Federation (sportgymrus.ru). Expert assessment of video materials from the World Championship and the Russian Cup 2023 on the channels: Match, allgymnastics.tv, FIG Channel. The research process included two stages - analytical and prognostic. At the first stage, an analysis was carried out of the regulatory documents of the IOC and FIG on the exclusion of Russian gymnasts from international competitions; information materials (format and program of competitions, statistics of results). At the second stage, a comparison of the results of the competition was carried out to predictably determine the model composition of the Russian national team, which could be currently competitive in the international arena. Results and conclusions. The pre-Olympic World Championship showed the absolute superiority of the US team with their leader S. Biles - the main contenders for winning the majority of gold medals at the XXXIII Olympiad in 2024. The sanctions imposed on Russian athletes did not allow Russian gymnasts, who would be the only team, to win a team license for the Olympic Games, which can compete with the US team in international competitions. Only in one all-around event are Russian gymnasts inferior to their foreign rivals - vault.